Unhealthy food pattern, physical activity, and the incidence of diabetes mellitus among adults with central obesity - Ahmad Syauqy; Amatulloh Dewi Fajar; Aryu Candra; Choirun Nissa (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
The prevalence of diabetes mellitus (DM) in Indonesia is increasing. A significant risk factor for developing DM is central obesity. Lifestyles, including diet and physical activity, strongly influence the high prevalence of DM and obesity. The study aimed to analyze the association between unhealthy food consumption and physical activity among adults with central obesity in Indonesia. This study used secondary data from Riskesdas 2018 with a cross-sectional design. The subjects in this study were adults (≥ 19 years old) with central obesity. A total of 7493 subjects were included in the analysis. Food intake data were taken using a validated FFQ, and physical activity using the GPAQ questionnaire. The data were analyzed using a chi-square test and multiple logistic regression. Frequent consumption of sweet foods (p=0,001, OR=1,235), sweetened beverages (p=0,042, OR=1,157), carbonated drinks (p=0,001, OR=1,324), instant noodles (p<0,001, OR=1,845), salty foods (p<0,001, OR=1,669), seasoning (p<0,001, OR=1,514), processed meats (p=0,009, OR=1,199), fatty foods (p<0,001, OR=1,687), and grilled foods (p<0,001, OR=1,243) were positively associated with the incidence of DM among adults with central obesity after adjusted with confounding variables. Low physical activity increased the incidence of DM among adults with central obesity in the unadjusted model (p=1,161, OR=1,161). In conclusion, there is a relationship between the consumption of unhealthy foods and physical activity with the incidence of DM in Indonesian adults with central obesity.